Neuromuscular Disorders A Comprehensive Review with Illustrative Cases - Khadilkar, Satish V. (Springer Singapore, 2018)
This book provides a concise overview of the diagnosis and therapy of a wide variety of neuromuscular disorders, in tabulated form and with illustrative cases. Treating neuromuscular disorders calls for a sound, step-by-step clinical approach based on differential diagnosis and laboratory investigations. Yet to date, there has been no single, compact book that offers all the relevant information related to the management of these disorders. This book fills that gap, presenting the state of the art in the field and addressing practical problems together with their solutions. Each chapter covers disorder characteristics, clinical differentiating points, relevant investigations and their interpretation, available genetic testing, best management approaches and counselling. Illustrative cases provide valuable insights, while extensive tables and illustrations mean that information can be rapidly found.